1999
DOI: 10.1103/physrevb.60.6574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the biquadratic interaction to magnetic surface reconstruction

Abstract: The surface spin ordering is studied in a ferromagnetic crystal where spins interact both by bilinear and biquadratic interaction. The surface spin configuration is unstable with respect to ferromagnetic alignment for certain values of parameters leading to so-called surface magnetic reconstruction. It is shown that biquadratic interaction enhances the reconstruction. The energy of surface excitations is calculated and it is shown to be much lower than the energy of bulk excitations in presence of surface reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Interactions such as biquadratic coupling, three-site four-spin interaction and four-site fourspin interaction have been discussed by many investigators. In particular, the practical interest in biquadratic interaction started when it had to be added to the usual bilinear Heisenberg exchange to explain some magnetic properties of materials, such as MnAs, TbSb, MnO, α-MnS, EuSe, rare-earth vanadates, arsenates, and phosphates [16]. Furthermore, it was shown that in some materials a biquadratic-like interaction is dominant (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions such as biquadratic coupling, three-site four-spin interaction and four-site fourspin interaction have been discussed by many investigators. In particular, the practical interest in biquadratic interaction started when it had to be added to the usual bilinear Heisenberg exchange to explain some magnetic properties of materials, such as MnAs, TbSb, MnO, α-MnS, EuSe, rare-earth vanadates, arsenates, and phosphates [16]. Furthermore, it was shown that in some materials a biquadratic-like interaction is dominant (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that in some materials a biquadratic-like interaction is dominant (see e.g. [16]). More recently, a strong biquadratic coupling has been found in magnetic metallic multilayers [17] and it is responsible for very interesting effects on the properties of the magnetoresistance and magnetization curves [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the practical interest in the biquadratic interaction started when it had to be added to the usual bilinear Heisenberg exchange to explain some magnetic properties of materials such as MnAs, TbSb, MnO, ␣-MnS, EuSe, rare-earth vanadates, arsenates, and phosphates. 3 Furthermore, it was shown that in some materials a biquadratic-like interaction is dominant ͑see, e.g., Ref. 3͒.…”
Section: Department Of Physics and Astronomy University Of Western Omentioning
confidence: 99%
“…Interactions such as biquadratic coupling, three-site four-spin interaction, and four-site four-spin interaction have been discussed by many investigators. In particular, the practical interest in biquadratic interaction started when it had to be added to the usual bilinear Heisenberg exchange to explain some magnetic properties of materials, such as MnAs, TbSb, MnO, α-MnS, EuSe, rare-earth vanadates, arsenates, and phosphates [7]. Furthermore, it was shown that in some materials a biquadratic-like interaction is dominant (see, e.g., [8]).…”
Section: Introductionmentioning
confidence: 99%